The influence of autistic symptoms on social and non-social cognition and on real-life functioning in people with schizophrenia: Evidence from the Italian Network for Research on Psychoses multicenter study - Antonio Vita; Stefano Barlati; Giacomo Deste; Paola Rocca; Alessandro Rossi; Alessandro Bertolino; Eugenio Aguglia; Mario Amore; Antonello Bellomo; Massimo Biondi; Bernardo Carpiniello; Enrico Collantoni; et al. (European Psychiatry, 2020)
Abstract